2015
DOI: 10.3310/phr03060
|View full text |Cite
|
Sign up to set email alerts
|

Population-level susceptibility, severity and spread of pandemic influenza: design of, and initial results from, a pre-pandemic and hibernating pandemic phase study using cross-sectional data from the Health Survey for England (HSE)

Abstract: BackgroundAssessing severity and spread of a novel influenza strain at the start of a pandemic is critical for informing a targeted and proportional response. It requires community-level studies to estimate the burden of infection and disease. Rapidly initiating such studies in a pandemic is difficult. The study aims to establish an efficient system allowing real-time assessment of population susceptibility, spread of infection and clinical attack rates in the event of a pandemic.MethodsWe developed and append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In our data set, people aged 25–35 were most likely to experience ILI and the over 65 age group were least likely to report ILI, consistent with other data from the pandemic . We have previously shown that ILIs reported in the HSE 2010 show a similar pattern and age distribution to infections identified in the Flu Watch cohort study, although the overall magnitude of ILI was considerably less. The Flu Watch cohort was designed to estimate the community burden of ILI by collecting data using active weekly prospective follow‐up but did not measure obesity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our data set, people aged 25–35 were most likely to experience ILI and the over 65 age group were least likely to report ILI, consistent with other data from the pandemic . We have previously shown that ILIs reported in the HSE 2010 show a similar pattern and age distribution to infections identified in the Flu Watch cohort study, although the overall magnitude of ILI was considerably less. The Flu Watch cohort was designed to estimate the community burden of ILI by collecting data using active weekly prospective follow‐up but did not measure obesity.…”
Section: Discussionsupporting
confidence: 88%
“…Recall bias, particularly in interviews taking place many months after illness due to the rolling nature of the survey, may have affected ILI reporting. 16 Mild symptoms, which were a typical feature of many infections in the 2009 influenza pandemic, may not have been attributed to ILI by participants. There is also a risk that media coverage of the pan- The use of weighting in analyses helped to ensure that participants selected were representative of the population at both regional and national level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population-level susceptibility, severity and spread of pandemic influenza study (PIPS) has developed the Health Survey for England as a tool for rapid population based serological surveys of influenza infection and disease [9]. During the first two waves of a pandemic, the study will assess the public's susceptibility to and spread of the novel virus both geographically and by age.…”
Section: The Nihr Crn Portfolio Of Pandemic Influenza Studiesmentioning
confidence: 99%
“…The PIPS study was specifically designed to piggyback on existing infrastructure provided by the Health Survey for England (HSE) [24], an annual, nationally representative, household survey which collects health information and blood specimens throughout the year [9]. This study is therefore dependent on the long-term continuation of the HSE and its continuation during a pandemic.…”
Section: Maintaining Engagement Of Research Sites To Ensure Rapid Actmentioning
confidence: 99%